Arduino-based Digital Advanced Audiometer - Hudha Wijaya, Nur; Ibrahim, Miftah; Shahu, Nishith; Usman Sattar, Mian (Journal of Robotics and Control (JRC), 2021)
The ear is an organ that is able to detect or recognize sound and also has a lot to play in the balance and position of the body. The ears are organs that are very vulnerable to noise. There are two common causes of hearing loss, namely decreased hearing conduction (hearing loss) and nerve hearing (sensorineural hearing loss). To prevent deafness, hearing control is necessary. Generally to test hearing function is done regularly by the ENT doctor at the hospital. This if done many times is deemed ineffective because it is time consuming and requires relatively expensive costs, therefore an early diagnosis of portable hearing loss is designed that is expected to be able to test independently independently over and over again. This tool is equipped with SD Card data storage, where the results of the data can be consulted by a doctor for further diagnosis. This tool uses an arduino uno R3 control, the frequency generator uses IC XR2206. The highest error is at the frequency of 8000 Hz which is 0.52%, but overall all systems on the device are functioning properly and the error is still within tolerance of 10%. From the results of these data, this tool can be recommended for early diagnosis of hearing function.